LINGUISTIC ANALYSIS OF SANTHALI - .M., Sathisha; V., Anand.; Rita N Kutty, N. Kutty,; Shobha., U.; P R, Lakshmisha (International Journal of Psychosocial Rehabilitation, 2021)
This paper is an attempt to highlight the minority status of the Santhali language, even though it was the first Indian tribal language to have its own script in the Wikipedia edition.At the turn of the 21st century there were approximately 6 million speakers of Santali, some 4.8 million of whom lived in India more than 150,000 in Bangladesh, and about 40,000 in tea districts in Nepal.(Anderson,2011). Though the language has its own Ol Chiki script, many Santhali tribal students do not have the option of studying Santhali in the secondary or higher secondary level, the reason being the lack of trained teachers and also due to lack of employment opportunities. Many Santhali tribal students even discontinue their studies due to these reasons. A lot still needs to be done till the Santhali language is treated on par with other scheduled Indian languages like Bengali, Oriya, Assamese etc.